IMPACT OF GOVERNMENT CAPITAL EXPENDITURE ON TRANSPORT, COMMUNICATION, ENERGY AND WATER SUPPLY ON ECONOMIC GROWTH IN SRI LANKA - Sooriyakumar, K.; Sireeranhan, A.; Sarujan, S. (My University, 2017)
This paper examines the effect of Sri Lankan government capital expenditure on transport and communication and energy and water supply on economic growth in Sri Lanka using cointegration regression. Infrastructure of transport and communication, consumption of electricity, gas and water play an important role in the modern economy. Without electricity new innovations and technological advancement are impossible. This study uses secondary time series data from 1998 to 2015. The results show that there is a long run relationship among government capital expenditure on transport and communication and energy and water supply on economic growth of Sri Lanka. The result of this study indicates that government capital expenditures on energy and water supply, transport and communication have positive impact on economic growth. Since energy and water are directly involved with production, capital expenditure on energy and water supply has greater impact on economic growth than the capital expenditure on transport and communication. Government expenditure on other economic services has negative impact on economic growth. This negative impact can be due to the bottle neck effect of government expenditure on private investment. This finding suggests that Sri Lankan government should invest more in the energy, water supply, transport and communication infrastructure than in the other economic services to accelerate the economic growth
Keywords: Economic Growth; Electricity; Infrastructure; Vector Error Correction Model